Impact of awe on topic interest and recognition memory for information in planetarium films - Kanerva, Oksana; Häikiö, Tuomo; Päällysaho, Helmi; Kaakinen, Johanna K. (Routledge, 2025)
We investigated the impact of situational awe on topic-specific interest and recognition memory for information presented in immersive planetarium films. Adult participants (N = 131) were recruited among science centre visitors who were going to view one of the films shown in the science centre’s planetarium. Participants responded to questions about prior knowledge, topic-specific interest in the film and background information before viewing one of the three planetarium films. After the film, they completed the topic-specific interest scale, epistemically-related emotion scales, situation-specific awe scale, critical thinking disposition scale and a recognition task of the film contents. The results showed that during viewing planetarium films participants experienced awe, but the strength of this emotion varied among films. Additionally, situation-specific awe was strongly associated with another epistemic emotion, namely surprise. As for the recognition task performance, awe decreased error and nonsense detection, and increased false recognition of inferential statements. Finally, awe was found to substantially increase topic-specific interest. These results present evidence that awe has potential to prompt individuals to become more interested in science-related topics.